Uma história intelectual do romance da Revolução Mexicana : escritores, camadas populares e ideias em circulação - Warley Alves Gomes (2021)
The present thesis seeks to present, as a central role, the intellectual history of Mexican Revolution's novel tradition throughout the 1910s to the 1960s. From this theme, four main points are developed. The first is a mapping of the representations about the Mexican Revolution elaborated from the trajectory of this literature that has created memories, imaginary thoughts and representations of the revolutionary process and its characters. There is also an analysis of three literary movements that acted as a counterpoint to these tradition: the Estridentismo, The Contemporáneos and the cristera literature. The second point is concentrated on the representations of three kind of actors in the Revolution: the popular layers, the revolutionary leaderships and the writers who represented themselves. The Emiliano Zapata's few appearances stand out, especially when compared to the Pancho Villa's wide presence in the works, which were also dedicated to represent the characters of Francisco Madero, Venustiano Carranza, Álvaro Obregón, Plutarco Elías Calles, Lázaro Cárdenas and Pascual Orozco. The third point deals with the writers insertion in the State structure and their relationship with the different governments, in effort of the "cultura revolucionária" construction, from the 1920s onwards. Thus, there were also analyzed the relationship between the State and the intellectuals who presented resistance to the project, as most Contemporáneos did. Lastly the fourth point is the formation of the Mexican Revolution's novel's tradition and the Mexican literature's memory itself of the 20th century's first half.